Norman Erikson Pasaribu, Happy Stories, Mostly. Trans. Tiffany Tsao. - Lee, Fiona (SARE: Southeast Asian Review of English, 2023)
A book review of the Indonesian short story collection by Norman Erikson Pasaribu titled, Happy Stories, Mostly (Tilted Axis Press, 2021). Translated into English by Tiffany Tsao, it was longlisted for the 2022 International Booker Prize.